2013
DOI: 10.11646/zootaxa.3692.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of calcareous sponges (Porifera: Calcarea) from the deep Antarctic Eckström Shelf and a revised list of species found in Antarctic waters

Abstract: The paper reports on two new species of calcareous sponges (Porifera, Calcarea) from the Antarctic Weddell Sea, Clathrina brandtae sp. nov. and Leucetta delicata sp. nov., collected at 600 m depth during the ANT XXIV/2-SYSTCO expedition in January 2008. The new species are described based on a combination of morphological and molecular data. With these new additions the number of species of calcareous sponges reported from south of 50°S (~south of the Polar Front) reaches 50 species. We report an exceptionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…The high degree of endemism has also been reported for other sponges in the Antarctic (e.g. Janussen & Tendal, 2007; Rapp et al , 2013) and extends to Antarctic deep-sea sponge communities, which instead are more closed elated to shallower Antarctic habitats (Göcke & Janussen, 2013). Asbestopluma (A.)…”
Section: Discussionsupporting
confidence: 54%
“…The high degree of endemism has also been reported for other sponges in the Antarctic (e.g. Janussen & Tendal, 2007; Rapp et al , 2013) and extends to Antarctic deep-sea sponge communities, which instead are more closed elated to shallower Antarctic habitats (Göcke & Janussen, 2013). Asbestopluma (A.)…”
Section: Discussionsupporting
confidence: 54%
“…Most of the currently known Antarctic sponge species were discovered during the oceanographic campaigns of the twentieth century [ 11 ], [ 12 ], [ 13 ], [ 14 ], [ 8 ], [ 15 ], [ 16 ], [ 17 ], [ 18 ], [ 19 ], [ 20 ], [ 21 ], [ 22 ], [ 23 ]. However, recent findings of many new species [ 24 ], [ 7 ], [ 25 ], [ 26 ], [ 27 ], [ 28 ], [ 29 ], [ 30 ], [ 31 ], [ 32 ] suggest that the sponge biodiversity of this area has not been fully explored yet and that more species remain to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…Van Soest (2001) allocated the polejaevi in the genus Leuconia , and following the most recent revision the name should be Leucandra (Borojevic et al , 2002b). As noted by Rapp (2006) presence of subcortical spaces is not unique for Pericharax within the Calcarea (Rapp et al , 2011, 2013; Klautau et al, 2013), and may also be found in some Leucandra . Except for the subcortical spaces and diactines slightly projecting through the cortex, L. polejaevi is almost identical with Leucandra egedii (Schmidt, 1869).…”
Section: Systematicsmentioning
confidence: 93%
“…Leucascus lobatus (Rapp, 2004a, b;Cavalcanti & Klautau, 2011;Rapp et al, 2011Rapp et al, , 2013Cavalcanti et al, 2013).…”
Section: Synonyms and Citationsunclassified